Sternotomy or Thoracotomy: Which One? - Tangkilisan, Adrian; Sukanto, Wega; Tamburian, Christha; Lolongan, Gerald R. (Universitas Sam Ratulangi, 2024)
Abstract: Penetrating injuries to the chest present a frequent and challenging problems. Median sternotomy and thoracotomy are two choices to explore any trauma to the chest. We report a 37-year-old man with wound and pain in his left chest due to being stabbed with a knife one hour ago. On physical examination, an open wound measured 5x1.5 cm as high as the third rib parallel to the left parasternal line, the edges of the wound bed were flattened by the periosteum. Laboratory examination showed leukocytosis. FAST showed an important left pleural effusion and pericardial fluid. CTA study showed the presence of air in the anterior mediastinum and the left pleural cavity. In the fifth intercostal space, a left anterolateral thoracotomy was performed and 800 ml of blood was evacuated from the left chest. The left lung was lowered to open the pericardium, which caused a further drop in blood pressure; then, the pericardium was opened and a blood clot (1500 ml) was removed. An epicardial wounds were found on the anterior surface of the right ventricle. The left anterior coronary artery was actively bleeding. The hemorrhagic lesion was stitched with 4.0 polypropylene reinforced with a Teflon strip. The patient recovered uneventfully on the sixth postoperative day. During the 14-month follow-up, the patient was fine and back to work. In conclusion, surgeon must be able to decide the technique of approach in the operating room considering the site of injury and the presence of involving organ. Thoracotomy patient can also receive median sternotomy if the cardiac injuries could not be repaired through thoracotomy. In addition, some patients with median sternotomy also received additional thoracotomy due to their pulmonary injuries. Keywords: penetrating injuries; thoracotomy; sternotomy; cardiac injury